Whistleblowing Policy in Education: Malaysian Perspective - Mohd Ali @ Ramli, Azlin Namili; A. Rahman, Aspalella; Yaacob, Nurli (2018)
The aim of this paper is to see whether the educational sectors in Malaysia has self-regulated whistle blowing policy. If none, then it is recommended that they ought to have one because people will not know how to report a wrong doing without the whistleblowing policy and will disclose it through wrong channels which might lead to chaos. This is a conceptual paper and an exploratory study on whistleblowing policy by educational sectors in Malaysia. This paper consists of introduction which include the definition of whistleblowing, law of whistleblowing in Malaysia and United Kingdom (UK), requirements of whistleblowing policy, whistleblowing policy in education sectors in Malaysia if any, and comparison with United Kingdom. Lastly, conclusion and suggestion on good concept of whistleblower laws that should exist in whistleblower policy. Many incidents showed that Malaysia education sectors do not have a formal self-regulated whistleblowing policy unlike United Kingdom and these lead to disclosing of wrong doings through media and create chaos to public